Dual Kidney Transplantation: Is It Worth It?. Issue 3 (March 2017) - Snanoudj, Renaud; Timsit, Marc-Olivier; Rabant, Marion; Tinel, Claire; Lazareth, Hélène; Lamhaut, Lionel; Martinez, Frank; Legendre, Christophe
Abstract : Abstract: Use of expanded criteria donor (ECD) kidneys, which are associated with a reduced graft survival rate, has become widely adopted in elderly recipients in an old-to-old allocation system. However, the results are frequently unsatisfactory, and a high proportion of these ECD kidneys are discarded. Dual kidney transplantation (DKT) is an underused way to expand the pool of ECD kidneys and to rapidly transplant elderly patients with satisfactory results because of the transplantation of double the nephronic mass. In this overview, we summarize the results of the main studies on DKT. DKT suffers from a prejudice of heaviness and is considered to be useless by transplant centers that do not perform it. The literature is often biased by the heterogeneity of the criteria leading to a DKT and the common refusal of kidneys that are judged too marginal. In fact, we show that when strictly allocated according to reliable clinical or histological scores, dual and single ECD transplantations yield similar results in terms of patient and graft survival rates despite significant differences in donors' characteristics. DKTs are not associated with a higher proportion of surgical complications, except in some studies showing thrombosis of 1 of the 2 grafts. The benefits of dual transplantation are particularly evident for kidneys coming from most ECDs. There is still a need for more studies to find the best allocation criteria that would permit transplantation to the highest number of patients with similar outcomes in recipients of single and dual ECD kidneys. Abstract : Dual kidney transplantation can expand the pool of ECD kidneys and to rapidly transplant elderly patients, but the best allocation criteria should be established to obtain the highest number of patients with similar outcomes in recipients of single and dual ECD kidneys.